High performance adaptive active harmonic filter design for non-linear led loads - TERZİ, ÜMİT KEMALETTİN (My University, 2022)
Today, illumination systems use approximately 1/3 of the electrical energy produced. For this reason, new technologies constantly increase energy efficacy in illumination technology. Consequently, the use of LED type light sources gets more widespread with low power electronics-based versions. The most important advantage of this type of systems has high luminous efficacy. However, since electronic systems have non-linear static loads, they cause unwanted harmonics in electrical distribution systems. Harmonics affect the operational safety as they cause unnecessary heating of the conductors in the electrical network. It also adversely affects the measuring and control systems of the buyers and so decreases the energy performance. In this study, an adaptive Butterworth low pass active harmonic filter model that can cut all current/voltage harmonics outside the operating frequency of different types of LED driver light sources is designed. In addition, harmonic analysis of different LED driver systems is performed experimentally by considering the total harmonic distortions (THD,%). In this way, harmonic components and (THD) values of different LED systems are obtained. These harmonic components obtained is filtered with the designed filter structure and the effects of the filter structure at each filtering degree on the harmonic components and THD were investigated. In this way, the designed filter is proved to be an adaptive model that can be adjusted automatically for different types of LED systems.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Fizik; Elektromanyetizma, Akustik, Isı Transferi, Klasik Mekanik ve Akışkanlar Dinamiği; Optik; Temel Bilimler; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Signal Processing; Physics; Electromagnetism, Acoustics, Heat Transfer, Classical Mechanics and Fluid Dynamics; Optics; Natural Sciences; Engineering and Technology; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); OPTİK; Temel Bilimler (SCI); ENGINEERING, ELECTRICAL & ELECTRONIC; ENGINEERING; Engineering, Computing & Technology (ENG); OPTICS; PHYSICS; Natural Sciences (SCI); Genel Mühendislik; Elektrik ve Elektronik Mühendisliği; Mühendislik (çeşitli); Fizik Bilimleri; General Engineering; Electrical and Electronic Engineering; Engineering (miscellaneous); Physical Sciences; harmonics; active harmonic filter; non-linear systems; op-amp power systems; LED illumination